Pengaruh Persepsi Harga Dan Kualitas Produk Terhadap Keputusan Pembelian Cat Nippon Paint (Studi Pada Pelanggan Cat Nippon Paint Di Gresik) - Muliawan P. Ashari; Supriono Supriono (Journal of Economic, Bussines and Accounting (COSTING), 2023)
When companies experience an increase in sales, it leads to profitability and sustains their business. One of the strategies is to improve product quality and setting appropriate pricing strategies. Enhancing product quality is necessary to retain customers and can also encourage other consumers to purchase the offered products. The objective of this study is to examine the influence of price perception and product quality on the purchasing decisions of Nippon Paint in Gresik. The population for this research was sampled using nonprobability sampling with a convenience sampling technique, with a total of 100 respondents. Data was collected using a questionnaire. Multiple linear regression analysis using IBM SPSS Statistics 22 was employed as the analytical technique in this study. Based on the test results, price perception has a significant influence on purchasing decisions, indicating that customers’ perception of the price plays a significant role in their decision making process. On the other hand, the study found that promotions have a non-significant impact on purchasing decision. Keywords: price perception; product quality; purchasing decision